Telegramming News: How have Telegram channels transformed the journalism in Iran? - Hossein Kermani (Türkiye İletişim Araştırmaları Dergisi)
This research tries to evaluate Telegram’s effects on journalism and news writing in Iran. The emergence of social media has affected many social and political trends in societies, as well as journalism practices and procedures. Telegram, as the most popular social media in Iran, hypothetically has the power to do so. Moreover, there are numerous channels on Telegram which publish news posts daily. Therefore, I tried to explore how these channels impact journalism in Iran. Doing so, I analyzed how the structure of news is transformed by the emergence of new forms of news writing and the disappearance of traditional standards. Furthermore, I probed the news values on Telegram channels to find out how a piece of writing becomes a news in this new space. Finally, I studied how objectivity was treated by Telegram channels, to provide a comprehensive interpretation of news on Telegram. A wide range of textual methods (both quantitative and qualitative content analyses and discourse analysis) were employed to analyze the most viewed posts on Telegram channels during Iran’s 2017 presidential election period. As a result, 620 posts in 31 days were gathered and analyzed. The results showed that the news structure has changed more than the ways that channels use news values. In fact, the old standards of news writing are abandoned and new forms, such as screenshots, have emerged. Moreover, prominence is the most favorable news value on these channels; while relevance and magnitude are of least interest. Finally, findings revealed that the majority of news posts are objective.